RIGHT TO PRIVACY AND PROTECTION OF A CHILD’S PERSONAL DATA (Multidisciplinary Journal of Science and Technology, 2026)
The article examines the right to privacy and the protection of children’s personal data in the context of digital transformation. It analyzes international legal standards and national legislation, as well as the specific features of implementing this right in the digital environment. Particular attention is paid to sharenting, parental control, and the formation of children’s digital identity. The study explores regulatory approaches to children’s data protection, including the principles of privacy by design and enhanced protection of vulnerable data subjects. The article substantiates the need for a comprehensive approach combining legal, institutional, and informational safeguards. It concludes that protecting children’s privacy in the digital age requires a balance between parental rights, state interests, and children’s emerging autonomy.